Legal Review Of Children Who Commit Traffic Violations - Eddy; Yasmira Mandasari Saragih; Tamaulina Br. Sembiring; Eri Siswanto (Yayasan Multidimensi Kreatif, 2025)
Traffic violations involving children are increasingly found in everyday life. Children, who in this case are categorized as a person under the age of 18, are often involved in various forms of traffic violations, such as driving a motor vehicle without a driver's license, violating traffic signs, riding and driving at dangerous speeds. This phenomenon raises concerns, especially due to the high risk of accidents and the potential for casualties. In this paper, we will discuss criminal liability for children who commit traffic violations and legal sanctions for children who commit traffic violations. The method applied in this study is the normative juridical method, a deductive approach that uses theory as a starting point to answer research questions. This study will analyze articles in laws and regulations related to legal studies of children who commit traffic violations. Legal sanctions against children who commit traffic violations can be in the form of criminal or non-penal actions. Criminal sanctions are more educational in nature such as warnings, supervision, and coaching in special institutions. Meanwhile, non-penal actions such as guidance or counseling are prioritized so that children can understand mistakes and correct their behavior. The system aims to ensure that children are given the opportunity to change. The application of sanctions against children who commit traffic violations must pay attention to the balance between law enforcement, the best interests of the child, and prevention goals. Despite violations, an approach based on the protection of children's rights remains the basis for coaching efforts.